Evaluation of the masticatory muscle function, physiological sleep variables, and salivary parameters after electromechanical therapeutic approaches in adult patients with Down syndrome: A randomized controlled clinical trial - Giannasi, Lilian Chrystiane [UNESP]; Dutra, Marignês T. S. [UNESP]; Tenguan, Vera L. S. [UNESP]; Mancilha, Gabriela P. [UNESP]; Silva, Gabriela R. C. [UNESP]; Fillietaz-Bacigalupo, Elaine [UNESP]; Da Silva, Daniel B. [UNESP]; Politti, Fabiano; Nacif, Sergio R.; De Oliveira, Ezequiel F.; Da Rocha, João C.; Rocha, Carolina T. [UNESP]; et al. (Springer Nature, 2019)
Background: There are many comorbidities associated with Down syndrome (DS), including obstructive sleep apnea (OSA) and masticatory muscle alteration. Muscular hypotonia, in particular, of the masticatory and oropharyngeal muscles is one of the main characteristics of individuals with DS, resulting in impairments of speech, swallowing, and mastication in these individuals. In addition, total or partial obstruction of the airways during sleep can occur due to pharyngeal hypotonia, leading to snoring and to OSA. This progressive respiratory disorder is associated with a high risk of morbidity and mortality in individuals with DS. The aim of this research is to assess the therapeutic effects of surface neuromuscular electrical stimulation (NMES), the mastication apparatus (MA), and a mandibular advancement oral appliance (OA m ) with an embedded thermosensitive microchip on the functions of masticatory muscles (bilateral masseter and temporal muscles), physiological sleep variables, and salivary parameters in adult patients with DS. Methods: The patients with DS will be randomly selected and divided into three groups (DS-NMES, DS-MA, and DS-OA m ) with a minimum of 10 patients in each group. A thermosensitive microchip will be embedded in the OA m to record its compliance. The therapeutic effects on masticatory muscle function will be investigated through electromyography, a caliper, and a force-transducer device; the sleep variables, in turn, will be evaluated by means of polysomnography. The physicochemical and microbiological properties of the saliva will also be analyzed, including the salivary flow, viscosity, buffer capacity, cortisol levels (susceptibility to psychological and/or physical stress), and Pseudomonas aeruginosa levels (risk of aspiration pneumonia) in these patients. The methods determined for this study will be carried out prior to and after 2 months of the recommended therapies. Discussion: The primary outcomes would be the improvement and/or reestablishment of the function of masticatory muscles and the physiological sleep variables in this target public since individuals with DS commonly present generalized muscular hypotonia and dysfunction of the oropharyngeal musculature. As a secondary outcome indicator, the impact of the applied therapies (NMES, MA, and OA m ) on the salivary microbiological and physicochemical properties in DS individuals will also be assessed. Furthermore, the compliance of OA m usage will be measured through a thermosensitive microchip. Trial registration: Registro Brasileiro de Ensaios Clínicos, RBR-3qp5np. Registered on 20 February 2018.
Keywords: Cortisol; Down syndrome; Electromyography; Masticatory muscles; Oral appliance; Polysomnography; Saliva; Sleep apnea